Religious Character Training Of The Learners Through The Training Of Yaumiyah Practice In SD Negeri 19 Kampung Baru Pariaman City - Astirani, Fuspita; Aguswan, Aguswan; Julhadi, Julhadi (Program Pascasarjana UMSB, 2024)
This study begins with the author's view of the habituation of Islamic practices at SDN 19 Kampung Baru, Pariaman City, namely tahfidz, infak, congregational Dhuhur prayer, sunnah Dhuha prayer, dhikr, and continued with prayer which is done before starting learning. In this regard, the school has a strategy, namely the Akhlak Star program which is used to trigger the enthusiasm of students in carrying out Islamic practices. This Akhlak Star is implemented from lower to higher classes. This activity is carried out routinely and consistently which is inseparable from the guidance of religious teachers and other educators. The habituation of Islamic practices is an effort to realize the foundation of pious and superior children. The habituation of Islamic practices aims for students at SDN 19 Kampung Baru to have religious character values. This research method is qualitative research with a descriptive analysis approach. Data collection in this study uses observation, interviews, and documentation. The data sources are Islamic religious education teachers, homeroom teachers, and the principal of SDN 19 Kampung Kota Pariaman. Data analysis is done by data reduction, data presentation, and data verification. The results of this study are that the author found religious character values in students during the implementation of the habit of Islamic practices, namely honesty, trustworthiness, responsibility, empathy, sympathy, friendliness, and creativity. Participants who have been accustomed to carrying out the habit of Islamic practices did not feel any objection. In fact, when the time came to carry out the habit of Islamic practices, they immediately rushed and carried it out. In addition, the moral star has three categories, namely personal moral star, class moral star, and infaq moral star. Students who meet the criteria for moral stars will be given a reward as a form of appreciation from educators. The moral star is a school institution initiative designed to encourage, strengthen, and appreciate good behavior as well as the development and improvement of student character. Keyword : Religious Character; Yaumiyah Practices; Islamic Education